Socialization of The Implementation of Psychosocial Development Screening for Preschool Children with Stunting In The Work Area Of Ngronggot Public Health Center - Nurhayati, Risa; Deppi Nurmalita; Pradita Ayu Rahma (Journal of Community Engagement in Health, 2025)
Stunting is a growth disorder that indicates problems with the body's organs, particularly the brain, which is vulnerable to damage. Conducting psychosocial development screening for stunted children has benefits in efforts for early detection and appropriate interventions to support the overall growth and development of children. Stunted children not only face obstacles in physical growth but are also at risk of experiencing delays in cognitive, emotional, social, and behavioral development. Therefore, a comprehensive approach through psychosocial screening becomes a strategic step to prevent more serious long-term impacts. This community service aims to conduct psychosocial development screening for preschool children experiencing stunting. The method used was to provide counseling to parents about psychosocial development, then conduct a psychosocial development screening practice using the KMME questionnaire followed by a question and answer session. The questionnaire was given in the form of closed-ended statements with two answer options: yes or no. The results obtained were good development (34.8%), poor development (65.2%). This community service shows that parents are capable of conducting psychosocial development screening for their children. Through this screening, parents can understand their child's psychosocial development and can enhance it through various efforts such as stimulation and parenting styles implemented within the family. The appropriate parenting style and developmental stimulation provided by parents to their children are expected to allow parents to recognize any abnormalities in their child's developmental process as early as possible, enabling them to provide comprehensive stimulation for the child's growth and development in physical, mental, and social aspects.